Brucellosis Initially Misidentified as Ochrobactrum anthropi Bacteremia: A Case Report and Review of the Literature. (1st October 2021) - Gopalsamy, Srinivasa Nithin; Ramakrishnan, Aditi; Shariff, Mustaf M; Gabel, Julie; Brennan, Skyler; Drenzek, Cherie; Farley, Monica M; Gaynes, Robert P; Cartwright, Emily J
Abstract: Automated identification systems may misidentify Brucella, the causative agent of brucellosis, which may be re-emerging in the United States as the result of an expanding feral swine population. We present a case of Brucella suis likely associated with feral swine exposure that was misidentified as Ochrobactrum anthropi, a phylogenetic relative.